Huuneh : incantation maya (lacandon) contre « la flèche de Kisin » - Didier Boremanse (Journal de la Société des Américanistes)
Lacandon oral tradition includes curing incantations which were believed to stop pains of a magical nature. The subject of the present study is a spell that is uttered to alleviate an acute and sudden pain that a person feels in a specific part of his/her body— arm, leg or chest. Such a pain is caused by an invisible arrow that has been shot by Kan Huuneh, a manifestation of Kisin, the evil god of the underworld. According to Lacandon beliefs, each person’s soul has a double which lives in the forest of the underworld in the shape of a spider-monkey. As Lacandon did in the past, Kisin hunts monkeys; and when his arrow pierces the arm, leg or chest of a monkey, the person whose soul’s double is that particular monkey feels the pain in the same part of her/his body. The incantation describes the technique of bow and arrow making, as well as the material used by Kan Huuneh/Kisin (for instance, the birds’ feathers he utilizes to feather his arrows), which does not fit at all Lacandon technical norms. The spell also mentions the places where Kan Huuneh might hide to shoot people, and finally it tells how Kisin’s arrow can be broken by the man who utters the magical words.